Development of Powtoon Animation Video Learning Media on Ferns Submaterial for Grade X - Titin Titin; Khairunnisa Khairunnisa; Asriah Nurdini (Bioeducation Journal, 2023)
Learning media are tools for teaching and learning that facilitate students' understanding of topics and play an important role in the teaching and learning process. Students can easily understand and use Powtoon animation video media for online and offline learning because it is provided in a beautiful and straightforward way. This research aims to determine the feasibility of the powtoon animation video learning media for class X ferns and students' responses to the powtoon animation video learning media for the X class ferns. This is a Research and Development study with seven stages: potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The Powtoon animation video media validation sheet validated by five validators, and student response questionnaires were used in this research. The participants of this research were grade X students of SMAN 1 Sungai Raya. The validation results on the powtoon animation video media which were assessed using the Aiken formula for media feasibility, material content feasibility, and language resulted in an average value of 0,90, so it was declared valid. The average value of student responses (cognitive, affective, and conative) in the small-scale trial was 87,8%, which was stated to be very strong. According to these results, it can be said that Powtoon animation videos on class X ferns can be used as an educational tool.